From Aphorism to Rubric: Integrating Organon of Medicine with Homoeopathic Repertory Through Clinical Case Analysis (Homoeopathy for All, 2026)
Background: The Organon of  Medicine forms the philosophical  and methodological foundation of  homoeopathic practice, while the  Homoeopathic Repertory functions  as a practical instrument for remedy  selection. Despite their intrinsic  interdependence, both subjects  are often taught and practiced in  isolation, leading to mechanical  repertorisation or philosophically  weak prescriptions. Aim: To demonstrate the integration  of Organon of Medicine with  Homoeopathic Repertory through  detailed clinical case analysis,  illustrating the transition from  aphorism-based reasoning to rubric based repertorial totality. Materials and Methods: An  observational, case-based clinical  study was conducted on patients  attending routine homoeopathic  OPD. Case taking, symptom  evaluation, and individualization  were guided by relevant aphorisms  from the Organon of Medicine.  Repertorial analysis was carried  out using standard homoeopathic  repertory, followed by individualized  prescription and follow-up. Results: Aphorism-guided reperto rial analysis enabled meaningful  rubric selection, accurate individu alization, and favorable clinical out comes in all cases presented. Conclusion: The Homoeopathic  Repertory is a practical extension of  the Organon of Medicine. An apho rism-to-rubric approach strengthens  clinical reasoning, preserves philo sophical integrity, and enhances  both teaching and practice of ho moeopathy.
Keywords: Organon of Medicine, Homoeopathic Repertory, Aphorism, Rubric, Individualization, Clinical Case Study